Effects of Homogenization Scheme of TiO2 Screen-Printing Paste for Dye-Sensitized Solar Cells. (1st March 2012) - Ito, Seigo; Takahashi, Kaoru; Yusa, Shin-ich; Imamura, Takahiro; Tanimoto, Kenji
Abstract : TiO2 porous electrodes have been fabricated for photoelectrodes in dye-sensitized solar cells (DSCs) using TiO2 screen-printing paste from nanocrystalline TiO2 powder dried from the synthesized sol. We prepared the TiO2 screen-printing paste by two different methods to disperse the nanocrystalline TiO2 powder: a "ball-milling route" and a "mortal-grinding route." The TiO2 ball-milling (TiO2 -BM) route gave monodisperse TiO2 nanoparticles, resulting in high photocurrent density (14.2 mA cm −2 ) and high photoconversion efficiency (8.27%). On the other hand, the TiO2 mortal-grinding (TiO2 -MG) route gave large aggregate of TiO2 nanoparticles, resulting in low photocurrent density (11.5 mA cm −2 ) and low photoconversion efficiency (6.43%). To analyze the photovoltaic characteristics, we measured the incident photon-to-current efficiency, light absorption spectroscopy, and electrical impedance spectroscopy of DSCs.